2019
DOI: 10.5507/bp.2019.059
|View full text |Cite
|
Sign up to set email alerts
|

Has the time come for de-escalation in the management of oropharyngeal carcinoma?

Abstract: Over the course of the last two decades, there has been a decrease in the incidence of head and neck cancers thanks to a decreasing prevalence of smoking. However, a new risk factor has been coming to the fore: human papillomavirus infection (HPV). HPV-positive oropharyngeal squamous cell carcinoma (HPV+OPC) is more sensitive to chemotherapy and radiotherapy, which translates to a much better prognosis with conventional treatment protocols than tumours that are HPV-negative. Traditional therapeutic interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Finally, traditional high-risk pathologic factors, such as extranodal extension (ENE), may not have the same prognostic significance or magnitude of importance in HPV-positive disease. 54 The indication for adjuvant chemotherapy for pathologic ENE (pENE) is based on evidence from 2 heterogeneous head and neck cancer trials, RTOG 9501 (Clini calTr ials.gov identifier NCT00002670) and European Organization for Research and Treatment of Cancer (EORTC) 22931 (Clini calTr ials.gov identifier NCT00002555), which were conducted before the HPV era. 55 Furthermore, there are conflicting retrospective reports on the survival impact of pENE in HPV-positive OPSCC.…”
Section: Clinical Prognostication Methods In Hpv-positive Opsccmentioning
confidence: 99%
“…Finally, traditional high-risk pathologic factors, such as extranodal extension (ENE), may not have the same prognostic significance or magnitude of importance in HPV-positive disease. 54 The indication for adjuvant chemotherapy for pathologic ENE (pENE) is based on evidence from 2 heterogeneous head and neck cancer trials, RTOG 9501 (Clini calTr ials.gov identifier NCT00002670) and European Organization for Research and Treatment of Cancer (EORTC) 22931 (Clini calTr ials.gov identifier NCT00002555), which were conducted before the HPV era. 55 Furthermore, there are conflicting retrospective reports on the survival impact of pENE in HPV-positive OPSCC.…”
Section: Clinical Prognostication Methods In Hpv-positive Opsccmentioning
confidence: 99%
“…10 In 2017 partial results were presented; at that moment the DFS at 2 years of the start of the study for the control group (Arm 2) was 87.5% versus 83.3% for the DI therapy (Arm 1). 8 Numbers of registers and other names NCT02254278/ NCT01706939/ NRG-HN002 9 Quarterback 10 Another RCT was found that met all inclusion criteria, but it is still an ongoing trial. It is the MR-ADAPTOR (NCT03224000), which plans, through individual control with weekly magnetic resonance imaging, to administer individualized CRT doses according to the response obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this more favorable prognosis, de-escalation protocols are being used at a higher rate [9]. However, there remains uncertainty regarding the best candidates for de-escalation therapy, as some patients have proved to be poor responders to these protocols [10,11]. There is a critical need to identify patient and tumor characteristics and biomarkers that can predict poor responders to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There is a critical need to identify patient and tumor characteristics and biomarkers that can predict poor responders to therapy. Currently, p16 status, tumor stage, and history of smoking are widely accepted as influencing prognosis in OPSCC [11]. Tumor and lymph node growth rates could potentially add to this growing list of prognosticators and assist in identifying patients who are appropriate for de-escalation protocols, or rather, intensification of treatment.…”
Section: Introductionmentioning
confidence: 99%